Endocrine disrupting chemicals and male fertility: from physiological to molecular effects - Marwa Lahimer; Marwa Lahimer; Marwa Lahimer; Maria Abou Diwan; Debbie Montjean; Rosalie Cabry; Rosalie Cabry; Véronique Bach; Mounir Ajina; Habib Ben Ali; Moncef Benkhalifa; Moncef Benkhalifa; et al. (Frontiers Media S.A., 2023)
The deleterious effects of chemical or non-chemical endocrine disruptors (EDs) on male fertility potential is well documented but still not fully elucidated. For example, the detection of industrial chemicals' metabolites in seminal plasma and follicular fluid can affect efficiency of the gametogenesis, the maturation and competency of gametes and has guided scientists to hypothesize that endocrine disrupting chemicals (EDCs) may disrupt hormonal homoeostasis by leading to a wide range of hormonal control impairments. The effects of EDCs exposure on reproductive health are highly dependent on factors including the type of EDCs, the duration of exposure, individual susceptibility, and the presence of other co-factors. Research and scientists continue to study these complex interactions. The aim of this review is to summarize the literature to better understand the potential reproductive health risks of EDCs in France.